Spatial differentiation and functional zoning of carbon budget: evidence from Jiangxi Province - Wenmei, Liao; Liwen, Jiang; Jiamin, Zou; Zhipeng, Wang; Hailan, Qiu; Shuie, Sun (Frontiers in Environmental Science, 2024)
Regional carbon budget and compensation are one of the current research hotspots, which is of great practical significance for dealing with climate change and promoting the coordinated development of low carbon. Based on energy consumption and land use data, a carbon budget and carbon compensation measurement model was established to analyze the change characteristics and spatial differentiation of the carbon budget of 11 prefecture-level cities in Jiangxi Province from 2010 to 2020 and carry out functional zoning, and further calculate the carbon compensation value of each prefecture-level city. The results showed that (1) during the study period, the carbon emissions in Jiangxi Province showed an increasing trend, with an average annual growth rate of 6.00 million tons, showing a spatial distribution pattern of “high in the west and low in the east.” The province was mainly represented by net carbon sources. (2) During the study period, the forest land in Jiangxi Province was the main carbon sink. The carbon sink absorption capacity declined from 60.56 million tons in 2010 to 59.69 million tons in 2020. (3) The regional difference in the economic contribution coefficient of prefecture-level cities in Jiangxi Province is relatively tiny. The ecological support coefficient has apparent spatial heterogeneity, showing a spatial distribution feature of “high in the south and low in the north.” (4) The 11 prefecture-level cities in Jiangxi Province could be divided into four regions: the carbon sink functional area, low-carbon optimization area, total carbon control area, and carbon intensity control area. By calculating the carbon compensation value and according to the difference in the carbon compensation value, the 11 prefecture-level cities in Jiangxi province are divided into four high-compensation areas, three low-compensation areas, and four compensated areas. The larger the carbon budget is, the higher the carbon compensation amount; conversely, the smaller the budget, the more carbon compensation amount can be obtained. According to the above conclusions, 11 prefecture-level cities should improve emission reduction mechanisms and strengthen the management of forest land utilization. Meanwhile, Jiangxi Province should formulate differentiated development, and compensation strategies should be developed to promote low-carbon, coordinated, and sustainable development among regions.